The Beudanticeratinae and Cleoniceratinae (Ammonitida) from the Lower Albian of Patagonia - Riccardi, Alberto Carlos (2002)
Albian Beudanticeratinae and Cleoniceratinae of the Patagonian Andes are revised taxonomically and chronologically, based on the re-examination of all available specimens and of most Albian localities of Santa Cruz Province, Argentina. Types and figured specimens of previously described species are reillustrated, but a few appear to be lost. Cleoniceratinae are represented by Cleoniceras PARONA & BONARELLI and Aioloceras WHITEHOUSE, and Beudanticeratinae by Beudanticeras HITZEL (?) and Uhligella JACOB. They include Cleoniceras? cf. santacrucense LEANZA, C. sp., Aioloceras argentinum (BONARELLI), A. rollerii and A. aff. rollerii (LEANZA), A. sp., Beudanticeras revoili (PERVINQUIERE), B. cf. laevigatum (J. de C. SOWERBY), B. sp., ?Uhligella sp. a and ?U. sp. b. Affinities with Beudanticeratinae and Cleoniceratinae from other areas of the globe are discussed. Because the type species of Aioloceras was based on two incomplete, juvenile, macroconch phragmocones, all previous diagnoses and systematics of Aioloceras based on these are inadequate. Paracleoniceras COLLIGNON is synonymous with Aioloceras and differences from Pseudosaynella SPATH and Grycia IMLAY are stressed. Inclusion of Aioloceras in Cleoniceratinae is based on ribbing, whorl section and the relatively simple septal suture with wide asymmetric L. Reports of Aioloceras from other continents are doubtful. Patagonian Beudanticeratinae and Cleoniceratinae are present in several sections between San Martin and Cardiel lakes, where they characterize stratigraphic levels. They are associated with other ammonoids, such as Douvilleiceras sp., Puzosia recteradiata COLLIGNON, Puzosia sp., Rossalites imlayi (LEANZA) and Pictetia ovalis COLLIGNON. This fauna belongs to the Aioloceras argentinum and to the A. rollerii (new) Assemblage Zones, coeval to the upper Lower Albian Mammillatum Superzone.